(untitled) (Innovative professional education, 2025)
The article examines the modern strategy of professional education development using digital technologies in the training of skilled workers in the conditions of war, post-war reconstruction and European integration of Ukraine. The main attention is paid to the key features and aspects of the use of digital technologies in vocational education, their integration to create an interactive and adaptive learning environment that ensures a high level of vocational training of future specialists. The advantages of implementing such technologies are analyzed, in particular, increasing the motivation to learn, developing practical skills, and the possibility of personalized learning. The use of digital platforms makes it possible to more effectively adapt the educational process to the needs of the modern market economy, contributing to the growth of the professional competence of graduates.